Effect of Hyperosmolar Solutions on Cerebral Oxygenation and Metabolism - S. S. Petrikov; V. V. Krylov; A. A. Solodov; Yu. V. Titova; Kh. T. Guseinova; L. T. Khamidova (Общая реаниматология)
Objective: to assess the time course of changes in the parameters of cerebral oxygenation and metabolism in the correction of intracranial hypertension with hyperosmolar solutions. Material and methods. 39 episodes of elevated intracranial pressure correction with 15% mannitol solution and HyperHAES solution were analyzed in 9 patients with intracranial hemorrhages. Changes in intracranial pressure and systemic hemodynamic, cerebral oxygenation, and metabolic parameters were studied. Results: A great difference was found in the effects of the test solutions on intracranial, cerebral perfusion pressure, and cerebral metabolism. Administration of 15% mannitol solution caused no cerebral metabolic changes. Infusion of HyperHAES solution induced a significant elevation in the concentrations of glucose and pyruvate in the interstitial fluid of both the arbitrarily intact and afflicted cerebral matter. Conclusion: The administration of 15% mannitol solution and HyperHAES solution is an effective method for correcting intracranial hypertension; however, the use of HyperHAES solution results in a more prolonged decrease in intracranial pressure, an increase in cerebral perfusion pressure, and an improvement of cerebral metabolism. Brain lesion due to intracranial hemorrhage may be accompanied by the development of mitochondrial dysfunction. Key words: intracranial hypertension, intracranial pressure, hyperosmolar solutions, tissue microdialysis.